Stakeholder approach in the management of public transport companies - Susnienė, Dalia; Jurkauskas, Algirdas (Transport, 2008)
The sustainable development of urban mobility cannot be envisaged without a transport system which could be able to meet the needs of citizens and businesses, make a positive impact on the environment and be socially fair and economically efficient. An efficient transport system increases safety, improves network efficiency and stimulates intermodality which reduces transport impact on environment and makes cities more attractive. In order to survive and successfully operate in the market, it is necessary for public transport companies to look for and implement new management models in their system. Every organization is surrounded by the environment and it is very important to examine external factors if an organization wants to gain a strong position in the market which is also important for public transport companies. The involvement of stakeholders in the supply of public transport services i.e. what level of relationships are needed between a transportation company and its various stakeholders is necessary in order to meet the main stakeholder ‐ passenger needs. Consequently, as to supply the passenger with the best service, relationships between different stakeholders (municipality, public transport company, state road maintenance service etc.) are of vital importance. It is essential to emphasise that state institutions and municipalities play a crucial role in managing public transport companies. State institutions influence them through legal instruments and regulations and municipalities, as the main shareholders, through the impact on management board and through subsidizing the company from municipality budget. Therefore, it is very important to have in mind this particularity in managing public transport companies and in the relationships with their stakeholders. First published online: 27 Oct 2010